Chicana Alliance Retreat 1980 - Chicana Alliance::::::::::::::: (2024)
Programs for the Chicana Alliance Retreat. Held on June 6-8. 1980 in La Selva Beach, California. Sponsored by San Jose State University, El Concilio, Semana Chicana, Women's Center, and Chicana Alliance.